Design briefs in design-driven new product development. (1st March 2019) - Parkman, Ian; Malkewitz, Keven
This study empirically examines the role of product design briefs as knowledge-based artefacts of cross-functional collaboration within design-driven new product development (NPD). Contemporary NPD is increasingly seen as a design-driven and knowledge-based activity where information sharing within team-based environments is critical to successful product design and development processes. However, the mere presence of inter-functional structures has not necessarily led to better outcomes for firms. By drawing on a proprietary sample of 80 product design briefs gathered from design-driven product-oriented firms, our results provide insight into how organizations create, codify and communicate knowledge from different functional areas and support flows of knowledge within NPD, specifically by: (1) providing an inventory of 51 information elements commonly present in product design briefs; (2) organizing these information elements into a parsimonious framework of strategic dimensions using exploratory factor analysis (EFA) alongside a widely-established taxonomy; (3) defining differences between information elements as rated by managerial 'importance' across three key functional areas of NPD: (a) design, (b) marketing and (c) engineering/ R&D/ development; and (4) providing a theoretic rationale for these differences and underlying strategic dimensions by integrating our findings with relevant literature.